2011
DOI: 10.1158/1078-0432.ccr-11-0951
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Autophagosome Vaccine: Mechanism of Cross-Presentation and Therapeutic Efficacy

Abstract: Purpose We previously reported that autophagy in tumor cells plays a critical role in cross-presentation of tumor antigens and that autophagosomes are efficient antigen carriers for cross-priming of tumor-reactive CD8+ T cells. Here we sought to characterize further the autophagosome-enriched vaccine named DRibble (DRiPs-containing blebs), derived from tumor cells after inhibition of protein degradation and provide insights into the mechanisms responsible for their efficacy as a novel cancer immunotherapy. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 48 publications
9
144
0
Order By: Relevance
“…Our studies demonstrated that antigens sequestered in the autophagosome may be delivered to DCs for cross-presentation and prime naïve antigen-specific CD8 T cells effectively (17). Subsequently, autophagosomes containing a broad spectrum of cellular antigens from antigen donor cells were collected by induction of autophagy and inhibition of lysosomal̸proteosomal activity, and named DRibbles (9,14,18,19). DRibbles have been demonstrated to exhibit vigorous antitumor efficacy in mouse experiments and cross-prime human CD8 T cells in ex vivo studies (10,11).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our studies demonstrated that antigens sequestered in the autophagosome may be delivered to DCs for cross-presentation and prime naïve antigen-specific CD8 T cells effectively (17). Subsequently, autophagosomes containing a broad spectrum of cellular antigens from antigen donor cells were collected by induction of autophagy and inhibition of lysosomal̸proteosomal activity, and named DRibbles (9,14,18,19). DRibbles have been demonstrated to exhibit vigorous antitumor efficacy in mouse experiments and cross-prime human CD8 T cells in ex vivo studies (10,11).…”
Section: Discussionmentioning
confidence: 94%
“…DRibbles was found to express abundant CLEC9A ligand and may directly bind to CLEC9A expressed on the surface of CD141 + cDC subsets. This suggests that the CD141 + cDC subset may be involved in the recognition or subsequent procession of DRibbles by DCs (14). In the presence of GM-CSF and IFN-α, monocytes may differentiate into IFN-DCs in vitro, which may have a more potent function in terms of CD8 T-cell cross-priming compared with traditional interleukin (IL)-4-DCs generated from monocytes stimulated by GM-CSF and IL-4 (13,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative mechanism underlying the increased cross-presentation potential of blebs is the presence of defective ribosomal products, which are present in the endoplasmic reticulum (an organelle actively translocated into blebs 20 ), potential TAAs that have been described to be efficiently cross-presented. 37,38 However, this concept is speculation, as we currently have no data to support this hypothesis. In any case, bleb-derived antigen is clearly efficiently ingested and cross-presented by skin DC and direct i.d.…”
Section: 1332mentioning
confidence: 95%
“…This results in accumulation of proteins including SLiPs and DRiPs in stable double-membrane autophagosomal vesicles that are isolated through cell disruption and differential centrifugation. 21-24 A human allogeneic autophagosome vaccine, DPV-001, comprising DRibbles derived from an adenocarcinoma (UbiLT6) and a mixed histology adenocarcinoma/squamous cell cancer (UbiLT3) cell line, has recently been tested in a randomized multi-center Phase II study for adjuvant treatment of definitively treated stage IIIA/B NSCLC patients and a pilot study for men with advanced prostate cancer. 24 Gene expression analysis of the two cell lines, UbiLT3 and UbiLT6, revealed that they highly express genes for a wide range of antigens common to adenocarcinomas and squamous cancers (unpublished data).…”
Section: Introductionmentioning
confidence: 99%